The Critical Power of the Residual. (17th November 2017) - Formis, Barbara
Abstract : In this essay, I intend to address the relationship between activities of maintenance and performance art, and in particular the feminist ramifications of this relationship. The aim is to identify what I call the 'power of the residual', the latter understood both as material leftovers (especially food waste) and as political minorities. The hypothesis is that if one thinks the power of residual, or the empowerment of what is left-out and left-behind, one brings about a dialectical change in perspective on the structure of society. This change in perspective reveals that 'left-out' agents are no longer to be considered the weaker part of society but in fact the stronger since they actually support, work for, care for and maintain the very equilibrium of society. I will first analyse Daniel Spoerri's art practice and his 'trap-paintings', and in the second part of the paper I explore the feminist aspects of performance with a particular focus on maintenance art and its ecological and sociological practices (Mierle Lademan Ukeles, Anna Halprin) . The objective is to understand the collective form of (food) sharing, and the ethical and political ramifications of maintenance as performance.